On logophagy and truth: Interpretation through incorporation among Peruvian Urarina. (November 2018) - Walker, Harry
Abstract: This paper develops an Amazonian critique of Western theories of interpretation as grounded in correspondence between a proposition and a state of affairs, and of truth as correspondence between mind and reality. For the Peruvian Urarina, language has materiality and force and implies a non-arbitrary relationship between signifier and signified, and is moreover based in a very different mode of adequation of person to world: a process grounded in absorption rather than representation. The view that words are effectively consumed by others is exemplified by the baau genre of ritual discourse, in which a healer's speech is literally digested by the patient as a core part of the healing process. Highlights: Western ideas of truth and interpretation tend to rely on ethnocentric assumptions. Amazonian Urarina ethnography implies a very different view of language. Words are essentially "eaten", implying a theory of absorptive truth. Similar views may be very widespread, albeit often largely implicit.